2019
DOI: 10.1038/s41598-019-40142-3
|View full text |Cite
|
Sign up to set email alerts
|

A basic Helix-Loop-Helix (SlARANCIO), identified from a Solanum pennellii introgression line, affects carotenoid accumulation in tomato fruits

Abstract: Carotenoid accumulation in tomato ( Solanum lycopersicum ) fruits is influenced by environmental stimuli and hormonal signals. However, information on the relative regulatory mechanisms are scanty since many molecular players of the carotenoid biosynthetic pathway are still unknown. Here, we reported a basic Helix-Loop-Helix transcription factor, named SlARANCIO (SlAR), whose silencing influences carotenoid accumulation in tomato fruits. The SlAR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Moreover, among the 16 genes, VIGS for two bHLH TFs (Solyc03g044460 and Solyc12g098620) showed green and light red phenotypes ( Supplemental Figure S1 ). Here, light red phenotype for Solyc12g098620 is in line with the recently published work by D’Amelia et al (2019) in which the authors reported that this bHLH TF regulates carotenoid biosynthesis. Additionally, one of the candidates, Solyc12g010950 (alcohol dehydrogenase), obtained a whitish green fruit phenotype, and another candidate, SlWD40 , obtained a yellowish fruit phenotype ( Figure 2 and Supplemental Figure S1 ).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, among the 16 genes, VIGS for two bHLH TFs (Solyc03g044460 and Solyc12g098620) showed green and light red phenotypes ( Supplemental Figure S1 ). Here, light red phenotype for Solyc12g098620 is in line with the recently published work by D’Amelia et al (2019) in which the authors reported that this bHLH TF regulates carotenoid biosynthesis. Additionally, one of the candidates, Solyc12g010950 (alcohol dehydrogenase), obtained a whitish green fruit phenotype, and another candidate, SlWD40 , obtained a yellowish fruit phenotype ( Figure 2 and Supplemental Figure S1 ).…”
Section: Discussionsupporting
confidence: 91%
“…Total anthocyanin amount was expressed as cyanidin 3-O-rutinoside as it was the main anthocyanin detected in tobacco in a previous study [38]. The evaluation of total carotenoids and chlorophylls was carried out according to Wellburn [39] and Zouari et al [40] with slight modifications [41]. Briefly, about 20 mg of sample was extracted with a solution of acetone/hexane (40/60, v/v) for 15 min.…”
Section: Pigments Profilementioning
confidence: 99%
“…In tomato, SlPRE2 , a gibberellic acid-induced bHLH TF, negatively regulates carotenogenesis by downregulating PSY and ZDS gene expression ( Zhu Z. et al, 2017 ; Zhu et al, 2019 ). Other bHLHs positively regulate carotenoid accumulation, such as papaya CpbHLH2, which activated expression of CYCB and LCYB in transient assays, and SlARANCIO, a tomato bHLH gene associated with a carotenoid QTL ( D’Amelia et al, 2019 ; Zhou et al, 2019 ). Fine mapping of the Y2 locus controlling beta-carotene accumulation in carrot found a differentially expressed bHLH TF, suggesting a potential regulatory role in carotenoid metabolism ( Ellison et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%